Factor contributing to the misuse of public space in the UNESCO World heritage site, George Town, Penang - Muhamad Ferdhaus Sazali (Universiti Pendidikan Sultan Idris, 2018)
Factor contributing to the misuse of public space in the UNESCO World heritage site, George Town, Penang by Muhamad Ferdhaus Sazali